SELNET clinical practice guidelines for soft tissue sarcoma and GIST. (January 2022) - Blay, J.Y.; Hindi, N.; Bollard, J.; Aguiar, S.; Angel, M.; Araya, B.; Badilla, R.; Bernabeu, D.; Campos, F.; Caro-Sánchez, C.H.S.; Carvajal, B.; Carvajal Montoya, A.; et al.
Highlights: Soft tissue sarcoma (STS) and gastrointestinal tumors (GIST) encompass > 80 different histologic subtypes. Clinical practice guidelines for STS and GIST still lack in Latin-American countries. Tailored clinical guidelines are instrumental to improve outcome in sarcoma patients in LatinAmerican countries. This is the first review establishing STS and GIST guidelines for the purpose of LatinAmerican clinical practices to our knowledge.